The Impact of Intrinsic and Extrinsic Motivation on Job Performance in a Participative Budget Setting: A Research Note - Zainuddin, Suria; Zainal, Dalilawati (Asian Journal of Accounting Perspectives, 2012)
Most of the studies that examine the variable for motivation only concentrate on either intrinsic or extrinsic motivation. However, this study highlights the importance of both types of motivation in increasing job performance. Specifically, the objective of this paper is to examine the impact of intrinsic and extrinsic motivation on job performance in a participative budget setting. Based on the survey questionnaire of 108 managers, data are analysed using Partial Least Squares. The results show that budget participation increases intrinsic motivation, and that intrinsic motivation leads to the extrinsic motivation, which, in turn, increases job performance.